Areas of Work Life as Burnout Predictors in Dentists of Denpasar, Indonesia - Sylvia Jessy Kurniawan; Kuswantoro Rusca Putra; Achmad Rudijanto; Wayan Agus Wirya Pratama (International Journal of Occupational Safety and Health, 2023)
Introduction: Burnout is most common among healthcare workers and is characterized by emotional fatigue, depersonalization and low personal accomplishment impacting behaviors also the work environment. This study aimed to analyze areas of work-life and burnout among dentists in dental hospitals.